KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM MENURUT BUKU KEPRBADIAN GURU KARYA ZAKIYAH DARADJAT - Suryani Suryani (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2016)
This studyaims to explain: 1) teacher personality Islamic religious education according to Zakiah Daradjat; 2)the personality of the islamic religious according to Zakiah Daradjat. The study uses a qualitative apporoach to the nature of the research library research and types of rsearch studies texs document. The result showed that: 1) The personality of the Islamic Religious education teacher according to Zakia Daradjat are: a) the physical aspects of the Islamic Religious education teacher’s personality include: sctions, speech, associanting, dressing; b) Psychological aspects of Islamic Religious Education include feelings and emotions; c) Sosial aspects of Islamic religious educations include; d) Attetion and affection; e) the Personality of the religious Education teacher Islamic aspect of religion. 2) Basic basic personality of teacher of Islamic religious education according to Zakiyah Daradjat is, a) juridical basis, on regulations government numbe 19 of 2005 cocerming stable, mature, wise and dignified, be a role model for student and have a noble character; b) Theological foundation, 1) Surah Al-Baqarah verse 32, namely the teacher al-‘alim personality never stops to learn and being wise means that a teacher always uses reson wise, wise when facing difficulties; 2) Surah Al-Muddatsir verses 1-7, namely the teacher gives warnings to students when violating norms, make his propession aware of Allah SWT, neat and clean in dress, leaving the prohibition of religious prohibition, no selfels and be patient both inside and outside the calsroom; 3) Surah Al-Lukman verses 12-19, namely teaching theachers to be grateful to Allah SWT and not associate Him, nti injustice. Not arrogant. Simplicity, and gentlensess; 4) Surah Al-Kahfi verses 60-82 namely the provide lessons for teachers to abstinence, deep despair achieve learning targets and goals, not shy to learn to other eductors or even their own students. Facing educational problems is not easy to judge or give a bad stamp to students, do not give punishment beyond the ability of students.